E-041 Safety and effectiveness of the pipeline embolization device in patients with nickel skin allergy. (22nd July 2018) - Wallace, A; Almandoz, J Delagado; Kayan, Y; Fease, J; Thomas, M; Scholz, J; Milner, A
Abstract : Introduction: The Pipeline Embolization Device (PED; Medtronic Neurovascular, Irvine, CA) has expanded the spectrum of aneurysms amenable to endovascular treatment. The device is a braided mesh cylinder composed of 48 strands of 25% platinum and 75% cobalt-nickel alloy. An estimated 17% of women and 3% of men are allergic to nickel, and the safety PED implantation in these patients is a concern. The purpose of this study was to assess the clinical and angiographic outcomes of PED treatment in patients with nickel allergy. Methods: A single institution neurointerventional database was retrospectively reviewed for patients treated with the PED who had a documented nickel allergy. In some patients patch testing was performed preoperatively, consisting of taping a PED to the patient's skin for 1 week. Patient demographics, aneurysm characteristics, and procedural details were recorded. All patients received dual antiplatelet therapy for approximately 17 days before treatment, and response was assessed with VerifyNow (Accriva Diagnostics; San Diego, CA). Follow-up digital subtraction angiography was performed 6 months post procedure. Longer-term follow up was performed with CT angiography when PED alone was used or MRA with and without contrast when adjunctive coiling was performed. Follow-up functional status was graded using the modified Rankin Scale (mRS). Good clinical outcome was defined as mRS ≤2 at last clinical follow up. Results: During the study period, 22 patients with documented nickel contact dermatitis underwent 23 PED treatments for 29 aneurysms. Patch testing was performed in 55% (12/22) of patients, none of whom experienced a skin reaction. The cohort included 21 women and 1 man with a mean age of 53.6±14 years. Patient medical comorbidities were as follows: hypertension, 40.9%; hyperlipidemia, 9.1%; type 2 diabetes mellitus, 0%. 36% (8/22) of patients actively smoked at the time of treatment. Mean aneurysm size was 8.8±8.1 mm (range, 2.0–32.0 mm), with 93% (27/29) located in the anterior circulation and 7% (2/29) in the posterior circulation. No aneurysms were treated in the setting of subarachnoid hemorrhage. Most patients were treated with a single PED (79.3%, 23/29). Five patients were treated with two PEDs and one was treated with three PEDs. 28% (8/29) of aneurysms were treated with adjunctive coiling. 18% (4/22) of patients experienced a symptomatic complication, all of which were thromboembolic, but all patients (100%, 22/22) had a good clinical outcome. During a mean angiographic follow-up of 16.2±13.0 months (range, 3–64 months), complete and near-complete (>90%) occlusion rates were 77% (20/26) and 4% (1/26), respectively. Endothelial hyperplasia occurred in one case (3%), which resulted in approximately 65% asymptomatic parent artery stenosis. Conclusion: All patients with nickel allergy treated with the PED had a good clinical outcome, but the thromboembolic complication rate was higher than typically reported for PED series. Further research is needed to determine if nickel allergy is an independent risk factor for procedural complications. Disclosures: A. Wallace: None. J. Delagado Almandoz: 2; C; Medtronic, Penumbra, Accriva, Microvention. Y. Kayan: 2; C; Medtronic, Penumbra, Microvention. J. Fease: None. M. Thomas: None. J. Scholz: None. A. Milner: None.